PEMETAAN SEBARAN TINGKAT BAHAYA EROSI DI WILAYAH SUB DAS LEMPAKE - Sri Sarminah; Triyono Sudarmadji; Oktavianus Surya Nata (ULIN: Jurnal Hutan Tropis, 2019)
This research was aimed to predict the erosion hazard level based on the Universal Soil Loss Equation (USLE) formula and to create distribution mapping of erosion hazard level at Lempake sub-watershed area. This research was conducted by overlay four types of maps, i.e: rainfall, soil, slope, and land cover maps.  The results showed that the process of overlay from a topographic map, map of soil types, vegetation maps and rainfall map was 36 land units about 583.108 ha area. Annual rainfall in the sub-watershed of Lempake during about 10 years old from the year of 2008 to 2017 amounted was 2445.8 mm. The soil type of dominant was podsolik kandika bout 1724 ha area. The most of topography of the Lempake sub-watershed was dominated by the slope class of 15-25% (rather steep) which is 1218.34 ha. Land covers were dominated by shrubs with an area of 830.27 ha. An overlay process was done to get the final result, i.e. erosion hazard level prediction. The level was classified into five categories those were very light, light, medium, heavy, and very heavy. The results showed that the distribution mapping of erosion hazard level at Lempake sub-watershed area ranged from very light to very heavy, with the percentage soft he affected areas are 20.39%;10.87%; 3.93%; 36.87%, and 27.9% respectively. The results can be used as a database to make a good planning watershed area management.